4x+a=-6

Simple and best practice solution for 4x+a=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+a=-6 equation:


Simplifying
4x + a = -6

Reorder the terms:
a + 4x = -6

Solving
a + 4x = -6

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-4x' to each side of the equation.
a + 4x + -4x = -6 + -4x

Combine like terms: 4x + -4x = 0
a + 0 = -6 + -4x
a = -6 + -4x

Simplifying
a = -6 + -4x

See similar equations:

| 4(2x+3)=21 | | 81650.99=2*3.14*2*r+2*314*r*287.9 | | 1/5b+19=3/5b-27 | | 9t^2+5=14t | | 15=7+10w | | c=25.34+.06*25.34 | | 15x-3-x=3x | | 218.75=35t-.7t^2 | | 3+8(x)=-29 | | 10m+8=6m-10 | | 1/4(72-6a)=-30 | | x*7=1200 | | 168=150(1+0.08) | | 3(x-3)+2=26 | | 580.586=2*3.14*18.49+2*3.14*4.3*h | | -3+8(1-2x)=4x-15 | | 3k+y=1 | | 2w+6x-y+8w-21x-7y= | | 95r=1995 | | -69v=-3450 | | (2+0.50)=10 | | 2=(0.50+10) | | 4q-9=27 | | 2(f-3)+9=5+f-1 | | 2-3x(8-6)= | | c=399+.06*399 | | 2y+1=1.5y+3 | | k-48=-6 | | T=.18*12.38 | | 2x+6=12x-12 | | 2(2+8v)= | | y+a=-21 |

Equations solver categories